Réveil peropératoire et memorisation: prévalence et aspects cliniques dans un Pays Sub-Saharien - Lankoandé, Martin; Bonkoungou, Papougnezambo; Konombo, Sylvain; Kaboré, Armel Flavien R; Napon, Christian; Sanou, Joachim; De waroux, Bernard Le Polain; Ouédraogo, Nazinigouba (European Scientific Journal, ESJ, 2017)
Objective: To study intraoperative memorization in the service of general surgery of Yalgado Ouedroago teaching Hospital (YO-TH) in Burkina Faso. Methods: It was a prospective study in the service of general surgery of YOTH over 7 months. The inclusion criteria were: age ≥ 18 years, absence of psychiatric disorder, American Society of Anesthesiology (ASA) score less than 4, informed consent written. Patients were interviewed at recovery. The questionnaire of Brice et al [8] was used and data were analyzed with SPHINX version 5.0.1 Results: A total of 475 patients were included. The mean age was 40.4 ± 16.3 years. The sex ratio was 1.4. The majority (56%) took psychoactive substance and 78.1% of patients had ASA score 2 or 3. Seven (1.4%) patients reported an explicit perioperative memorization (EPOM +). The mean age of EPOM + patients was 26.8 ± 6.57 years with a sex ratio 1.3. There was difference between EPOM + patients and EMPO - for age (p = 0.0001), occupation (p = 0.009) and antecedent of local anesthesia (p = 0.004). Five patients reported auditory perceptions, four cases of visual perceptions and two tactile perceptions. Pain was the most unpleasant memorization recorded. The psychological consequences of EPOM + were anxiety (2 cases). Conclusion: The frequency of EPOM is low in our context and the main cause was a slight anesthesia.